REALIZING AN ORDERLY AND REGULAR TELEVISION AND BROADCASTING INFRASTRUCTURE AS A MEDIUM OF INFORMATION AND COMMUNICATION - Rosalinda Pranita; Muhamad Arif Setiawan (Jurnal Prodi Ilmu Komunikasi, 2022)
The purpose of this research is so that the public as well as television and radio station institutions can better understand the procedures in managing the structure and broadcasting system as well as to provide information and an invitation to the entire community to change their mindset and be more careful in watching TV broadcasts and listening to the radio. and report if there are illegal (illegal) tv or radio stations. This study uses a qualitative descriptive method, data collection techniques using interview techniques, observation, and South Sumatra KPID documents or data. The subjects of the research are informants who have an interest in licensing and monitoring broadcast content at the South Sumatra KPID. Based on the results of the study, it can be concluded that in order to organize broadcasting, one must obtain a license to organize broadcasts in accordance with the procedures and requirements for establishing a broadcasting institution and television and radio information must provide healthy broadcasts to the public because what is assumed will change their behavior. Broadcasting of broadcast content must comply with the Broadcasting Code of Conduct (P3) and Broadcast Program Standards (SPS).